Clinico-biochemical profile and etiology of acute viral hepatitis in hospitalized children: A study from Eastern India - Behera, Manas Ranjan; Patnaik, Lipilekha (Indian Journal of Child Health, 2016)
Background: Acute viral hepatitis (AVH) in children continues to be a major public health problem in India. Objective: To identify the etiology, and to assess the clinical and biochemical profile, complications and outcome of AVH in children. Materials and Methods: A total of 76 children with the clinical diagnosis of AVH were included in this record based retrospective study from January 2014 to August 2016. Data on clinical characteristics, laboratory parameters, immediate outcome, and treatment received were obtained, and analysis was performed. Results: Specific etiological agents were identified in 84.2% children. Out of these, 93.7% were due to a single virus, whereas 6.3% were due to mixed infection. Hepatitis A virus (HAV) was found to be the sole infecting agent in 75% children. Hepatitis B virus (HBV) and hepatitis E virus (HEV) were found in 12.5% and 6.2% children, respectively. Mixed infection was seen in the form of HAV and HEV in 3.1%, and HAV and HBV in 3.1%. The mean age of children with hepatitis A was 8.29±2.74 years, with 70.8% boys and 29.2% girls. Common clinical features were jaundice (95.8%), loss of appetite (95.8%), tender hepatomegaly (68.8%), fever (50%), vomiting (50%), pain abdomen (33.3%), splenomegaly (31.2%), itching (27.1%), bleeding (2.1%), and seizure (2.1%). Acute liver failure was seen in 4.1% and 2% of admitted children died. The mean age of presentation of AVH due to HBV and HEV were 10.7±2.6 years and 10±2.2 years, respectively. Clinical features were similar without any complications or mortality. Significant elevations in hepatic enzymes were seen in mixed infection due to HAV and HEV (p<0.05). Conclusion: HAV is the primary cause of morbidity and mortality due to AVH in this region. HBV and HEV infection may present with similar clinical features, and serological testing must be done to identify the cause.